Reflections on the battle against COVID-19: The effects of emotional design factors on the communication of audio-visual art - Fang, Wen-Ting; Sun, Jian-Hua; Liang, Qing-Dong (Frontiers in Psychology, 2022)
Fighting against the epidemic is an arduous and prolonged battle where many artists hope to inspire people with the power of art through cultural creativity. To explore the effects of emotional design factors on the communication of audio-visual art and the audience’s perceptive experience, this research takes the original anti-epidemic song and the film China Braves Headwind as the research object. The research also uses such methods as questionnaires, Structural Equation Model, and dependent samples t-tests to conduct statistical analysis. The results are as follows: First, the emotional design evaluation matrix based on the emotional communication model is reasonable, and the scales of this research are feasible. Second, the emotional design of audio-visual works can significantly affect the audience’s emotional experience and further improve sharing intention. Third, Attribute A2 (Artistic style, Thematic perception) and attribute C3 (Emotional resonance, Spiritual sublimation) serve as common factors affecting the emotional experience in terms of both musical works and film & television works. Forth, compared with musical works, film & television works are likely to resonate with the audience. The combination of music and visual sensation can help open up the conception of artistic works and convey their meanings to viewers. Therefore, it’s necessary to explore the emotional communication mode between audio-visual artists and the audience. It helps artists think about how to create works innovatively and is conducive to marketizing works and stimulating cultural consumption demand.